2019
DOI: 10.1136/esmoopen-2019-000535
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy in combination with systemic therapy for metastatic renal cell carcinoma: a prospective multicentre study

Abstract: BackgroundTyrosine kinase inhibitors (TKIs) and checkpoint inhibitors have been established as effective treatment for metastatic renal cell carcinoma (mRCC), but only a minority of patients achieve complete response. Additional strategies are necessary to improve these agents’ efficacy.MethodsPatients with stable disease for at least 4 months on TKI or checkpoint inhibitors were included. Stereotactic body radiotherapy (SBRT) was delivered to an organ with comparable lesions, where one lesion was in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…In a recent phase I/II study including 13 patients treated with Pazopanib and SBRT local control and response rates outside the radiation field were good but seemed not to be superior when compared to SBRT or Pazopanib in monotherapy [52]. Contrarily, Dengina et al [53] observed in a small phase 1b Volga Study (VEGFR inhibitor or mTOR inhibitor or checkpoint inhibitors and SRT) that the difference in response in the target and control metastases evaluated by a mean size of the lesions before and at 2 months after SBRT was statistically significant (p < 0.01). Miller et al [54] demonstrated in the multivariate competing risks regression that concurrent first-line TKI treatment was independently associated with a local control benefit (HR 0.21, p = 0.04), while patients treated with TKIs alone experienced an increased rate of local failure (HR 2.43, p = 0.03).…”
Section: Target Therapy and High Doses Rtmentioning
confidence: 98%
“…In a recent phase I/II study including 13 patients treated with Pazopanib and SBRT local control and response rates outside the radiation field were good but seemed not to be superior when compared to SBRT or Pazopanib in monotherapy [52]. Contrarily, Dengina et al [53] observed in a small phase 1b Volga Study (VEGFR inhibitor or mTOR inhibitor or checkpoint inhibitors and SRT) that the difference in response in the target and control metastases evaluated by a mean size of the lesions before and at 2 months after SBRT was statistically significant (p < 0.01). Miller et al [54] demonstrated in the multivariate competing risks regression that concurrent first-line TKI treatment was independently associated with a local control benefit (HR 0.21, p = 0.04), while patients treated with TKIs alone experienced an increased rate of local failure (HR 2.43, p = 0.03).…”
Section: Target Therapy and High Doses Rtmentioning
confidence: 98%
“…These findings have sparked further interest in the use of available tumor-modulating agents, including radiation, to sensitize patients to immunotherapy. With mounting questions surrounding the synergy between immune therapies and SBRT (6,17), there is an urgent need to understand how radiation impacts the tumor immune landscape in patients.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the ability of high-dose radiation delivered with SBRT to control RCC growth ( 12 16 ). In addition, clinical trials that combined SBRT with IL-2, immune checkpoint blockade (ICB), or tyrosine kinase inhibition have shown promise in treating RCC ( 6 , 7 , 17 ).…”
mentioning
confidence: 99%
“…In another prospective study, patients were treated with SRT in combination with tyrosine kinase inhibitor or ICI. Thirteen of 17 patients (76%) achieved partial response (47%) or complete response (29%) 10 . These results suggest that radiotherapy could enhance the efficacy of systemic therapy.…”
Section: Discussionmentioning
confidence: 85%